Adaptive Delta-Sigma Modulation for Enhanced Input Dynamic Range. (29th June 2008) - Zierhofer Zierhofer, Clemens M. Clemens M.
Abstract : An adaptive delta-sigma modulator of 1st order with one-bit quantization is presented. Adaptation is instantaneous and based on an exponential law. The feedback signal is a multibit discrete-level signal generated by a digital-to-analog converter (DAC). Compared to a nonadaptive delta-sigma modulator of 1st order, the input dynamic range is significantly enhanced. The gain in dynamic range is 6 dB per bit defining the feedback amplitude. The influence of nonideal DAC performance is discussed. It is demonstrated that an implementation of the system is realistic with standard CMOS technology. To relax the requirements to the one-bit quantizer, the quantizer input signal is amplified adaptively (Q-Switching).